PEMANFAATAN MARKETPLACE SHOPEE SEBAGAI MEDIA KOMUNIKASI PEMASARAN TOKO PUTRI INDAH - Utari, Tri; Sariwaty, Yulia (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Companies are experiencing major changes in their approach to consumers as a result of the digital revolution. The internet allows consumers to analyze prices, compare the quality of goods through other consumer reviews in the comments column, and provide an objective assessment. This research was conducted to study the mar-keting communication strategies used by the Putra Indah online shop. This study used a qualitative method using data collection procedures through interviews, observation, and documentation. The approach used in this research is descriptive. The results of the study show that the Putra Indah online shop charges a slightly lower price than the average price of other sellers taking into account the regulations of the shopee. The Putra Indah online shop often participates in shopee events and programs and utilizes available features to support its marketing communications, including store promo features, discount packages, shop follow vouchers, my shop vouchers, and seller chat. Inhibiting factors include mistyped addresses by customers, lack of response from customers on purchases of goods, and lack of reviews after customers receive products. On the other hand, there are marketing supporting factors such as utilizing available features, and participating in events and programs held by shopee.